Pengaruh Ice Breaking Terhadap Motivasi Belajar Siswwa SMP Terpadu Darul Dakwah - Deka Anjariyah; Mochammad Fairus Abadi; Novaria Saputri; Anggun Triya; Desy Yantene; Rahma Nur Qabibi; Sita Oktavia Sari; Alvin Ardhiansyah; Muhammad Amaruddin (Indonesian language and literature education program Majapahit Islamic University, 2023)
This research aims to determine the effect of icebreaking on student learning motivation at Terpadu Darul Dakwah Junior High School which will be carried out in the 2023/2024 academic year. Ice breaking is a straightforward, light and concise action that is able to change stiffness, determination, fatigue or lethargy in learning activities so that it can create a learning atmosphere that is full of energy and fun. The type of research used is quantitative. The population in this study was 200 students at Terpadu Darul Dakwah Junior High School with a sample of 62 students in grades 7, 8, 9. The instrument used in this research is a learning motivation number. Researchers also used data collection techniques using learning motivation questionnaires which were given to students in the form of questionnaires before and after icebreaking in learning to determine the effect of this activity on students' learning motivation. The results of the research show that the presence of icebreaking during classroom learning activities has an effect on students' learning motivation. Keywords: Ice breaking, Motivation, Influence